EARLY CHILDHOOD PARENTING: THE ROLE OF PARENTAL MINDFULNESS AND COPARENTING COMPETENCE IN PARENTAL WELL-BEING - Mafaza Mafaza; Septi Mayang Sarry (Journal of Psychological Science and Profession, 2022)
Parents' well-being are significant things. Well-being is not only counted for parents’ physical, emotional, and mental conditions as an individual, it also has enormous influences on various aspects of children's development. Parents tend to face challenges, difficulties, and pressures during parenting, especially when caring for children in early childhood. This study aims to determine the role of parental mindfulness and coparenting competence in predicting parental well-being. Three hundred and thirty-one parents of children in early childhood participated in this study. The researchers used the convenience sampling method. Parents completed the Parental Well-Being Scale, Bangor Mindful Parenting Scale, and Coparenting Competence Scale. The result of multiple linear regression analysis indicated that parental mindfulness and coparenting competence have significant roles in predicting parental well-being. The coefficient of determination showed that parental mindfulness and coparenting competence simultaneously explained 15.7% of the parental well-being variance. There are no significant differences in parental well-being between fathers and mothers. This finding indicates the importance of parenting competence in order to improve parental well-being.